Nuclear-encoded mitochondrial tRNAs of Trypanosoma brucei have a modified cytidine in the anticodon loop. - Schneider, A (1994)
The mitochondrial genome of Trypanosoma brucei does not appear to encode any tRNA genes. Isolated organellar tRNAs hybridize to nuclear DNA, suggesting that they are synthesized in the nucleus and subsequently imported into the mitochondrion. Most imported tRNAs have cytosolic counterparts, showing identical mobility on two-dimensional polyacrylamide gels. We have compared three nuclear-encoded mitochondrial tRNAs (tRNA(Lys), tRNA(Leu), tRNA(Tyr)) with their cytosolic isoforms by direct enzymatic sequence analysis. Our findings indicate that the primary sequences of the mitochondrial and the corresponding cytosolic tRNAs are identical. However, we have identified a mitochondrion-specific nucleotide modification of each tRNA which is localized to a conserved cytidine residue at the penultimate position 5' of the anticodon. The modification present in mature mitochondrial tRNA(Tyr) was not found in a mutant tRNA(Tyr) defective in splicing in either cytosolic or mitochondrial fractions. The mutant tRNA(Tyr) has been expressed in transformed cells and its import into mitochondria has been demonstrated, suggesting that the modified cytidine residue is not required for import and therefore may be involved in adapting imported tRNAs to specific requirements of the mitochondrial translation machinery.